A preliminary study on the benefits of loyalty programs in Malaysian city hotels / Jazira Anuar, Norzuwana Sumarjan and Salleh Mohd Radzi - Anuar, Jazira; Sumarjan, Norzuwana; Mohd Radzi, Salleh (UiTM Press, 2013)
Hotels spend millions of dollars annually to grant benefits to their loyal members. However, despite having a huge portion of invest-ment on this loyalty program benefits, the effectiveness of such pro-grams in delivering benefits to members is still questionable. In-depth interviews of 14 hotel executives from either Front Office or Marketing department were primarily conducted to explore hotel’s benefit structures. The taxonomical benefits offered by six city hotel loyalty programs were compared and summarized. The transcripts and tapes derived from the interviews were analyzed, coded and summarized into categories. The findings were structurally com-pared. Findings revealed that although these six city hotels sharing the same thirteen core benefits, but each hotel is trying very hard to differentiate themselves from their competitors. It is beneficial for hoteliers in improving their current loyalty programs or designing new loyalty programs for their hotel. Uniquely, this study provides benefit taxonomy summary of the six city hotel loyalty programs in Malaysia and compares the benefits categorized into three levels: core benefits, partially common benefits and individual benefits.